Renal replacement therapy in Latin American end-stage renal disease - Rosa-Diez, Guillermo (Oxford University Press, 2014)
The Latin American Dialysis and Renal Transplant Registry (RLADTR) was founded in 1991; it collects data from 20 countries which are members of Sociedad Latinoamericana de Nefrología e Hipertension. This paper presents the results corresponding to the year 2010. This study is an annual survey requesting data on incident and prevalent patients undergoing renal replacement treatment (RRT) in all modalities: hemodialysis (HD), peritoneal dialysis (PD) and living with a functioning graft (LFG), etc. Prevalence and incidence were compared with previous years. The type of renal replacement therapy was analyzed, with special emphasis on PD and transplant (Tx). These variables were correlated with the gross national income (GNI) and the life expectancy at birth. Twenty countries participed in the surveys, covering 99% of the Latin American. The prevalence of end stage renal disease (ESRD) under RRT in Latin America (LA) increased from 119 patients per million population (pmp) in 1991 to 660 pmp in 2010 (HD 413 pmp, PD 135 pmp and LFG 111 pmp). HD proportionally increased more than PD, and Tx HD continues to be the treatment of choice in the region (75%). The kidney Tx rate increased from 3.7 pmp in 1987 to 6.9 pmp in 1991 and to 19.1 in 2010. The total number of Tx's in 2010 was 10 397, with 58% deceased donors. The total RRT prevalence correlated positively with GNI (r(2) 0.86; P < 0.05) and life expectancy at birth (r(2) 0.58; P < 0.05). The HD prevalence and the kidney Tx rate correlated significantly with the same indexes, whereas the PD rate showed no correlation with these variables. A tendency to rate stabilization/little growth was reported in the most regional countries. As in previous reports, the global incidence rate correlated significantly only with GNI (r(2) 0.63; P < 0.05). Diabetes remained the leading cause of ESRD. The most frequent causes of death were cardiovascular (45%) and infections (22%). Neoplasms accounted for 10% of the causes of death. The prevalence of RRT continues to increase, particularly in countries with 100% public health or insurance coverage for RRT, where it approaches rates comparable to those displayed by developed countries with a better GNI. The incidence also continues to increase in both countries that have not yet extended its coverage to 100% of the population as well as in those that have an adequate program for timely detection and treatment of chronic kidney disease (CKD) and its associated risk factors. PD is still an underutilized strategy for RRT in the region. Even though renal Tx is feasible, its growth rate is still not as fast as it should be in order to compensate for the increased prevalence of patients on waiting lists. Diagnostic and prevention programs for hypertension and diabetes, appropriate policies promoting the expansion of PD and organ procurement as well as transplantation as cost-effective forms of RRT are needed in the region. Regional cooperation among Latin American countries, allowing the more developed to guide and train others in starting registries and CKD programs, may be one of the key initiatives to address this deficit.